Preservice physical education teachers’ professional action competence in education for sustainability: a mixed method research - Royet, Thomas; Cece, Valérian; Lentillon-Kaestner, Vanessa; Castéra, Jérémy; Vors, Olivier (Frontiers in Psychology, 2025)
IntroductionWith the growing emphasis on sustainability, physical education (PE) teachers are expected to incorporate education for sustainability (EfS) into their teaching. Based on a mixed method, this study aimed to assess preservice PE teachers’ professional action competence in EfS (PACesd) and identify PACesd profiles.MethodsA total of 412 French preservice PE teachers completed a questionnaire measuring PACesd, along with open-ended questions enabling an external assessment of pedagogical content knowledge. Descriptive statistics, correlation analysis, and latent profile analysis were conducted to identify PAC profiles. Thematic analysis based on both qualitative and quantitative approaches was used on open-ended responses, allowing chi-square tests to identify differences across PAC profiles.ResultsThe results revealed moderate-high perceived pedagogical content knowledge and self-efficacy but low willingness to teach EfS. Four competence profiles emerged, with external assessment revealing key similarities and differences.DiscussionThese results highlight the need for targeted professional development to support EfS integration in PE.